Nilai-Nilai Kearifan Lokal Pada Penciptaan Kapal Kayu Tradisional Pesisir Riau dalam Kajian Sosiologi-Antropologi - Hambali, Hambali; Hariyanti, Hariyanti; Eddison, Ahmad (Journal of Moral and Civic Education, 2023)
Traditional wooden shipbuilding can be seen from different perspectives, namely from industry and tradition and culture. As a tradition and culture, traditional wooden shipbuilding is a means of developing character and local wisdom which is closely related to the life of the people involved. Thus, this study aims to analyze the values of local wisdom in the creation of traditional wooden boats in the coastal areas of Riau and the Riau Archipelago. Research is the result of analysis of qualitative methods with data collection techniques through observation and interviews. The results of the study from the socio-anthropological review show that the culture and tradition of creating traditional wooden boats for coastal Malay communities is influenced by foreign cultures, forming a national identity, the knowledge possessed by craftsmen (workers) in shipbuilding is manual even though the size of the ships made is relatively large enough to 1,500 GT. In addition, the existence of these traditional wooden boats is considered sturdy so that they are in demand and widely used by world fishermen, especially in the archipelago. However, currently the existence of traditional wooden boats is becoming scarce due to the difficulty of raw materials. The character values of local wisdom contained in the creation of traditional wooden ships are hard workers (my ancestors were sailors). Among the national character values are: work hard (work hard), act correctly, be trustworthy, maintain unity, not destroy nature (love the environment), and so on.